The religion of whiteness: how racism distorts Christian faith - Emerson, Michael O. (Oxford University Press, 2024)
"We offer a new perspective that this inequality is perpetuated because it is a necessary feature of a religion, a religion practiced and held dearly by millions of people. That religion, which we label the Religion of Whiteness, raises racial interests to the level of spiritual commitment rivalling followers' commitment to Christianity itself. The Religion of Whiteness, a sect within historical Christianity, has risen to canonical status in many churches and among its millions of followers. This religion has its own unique beliefs, practices, sacred symbols, and organizations. It drives the nation's politics, divides families, and is especially harmful to communities of color. Using national survey data, in-depth interviews, and focus group results over several years of study, we show how the Religion of Whiteness distorts the practice of traditional Christianity for millions of Americans. We find that the Religion of Whiteness has two distinct but mutually constitutive groups, what we call the White Veil and the White Might groups. These two groups work to defend and uphold the Religion of Whiteness, at great costs to any who do not follow the religion. If churches hope to promote traditional Christianity and navigate the very many contentious issues of the nation, they must confront the distorting power of the Religion of Whiteness. We conclude with a suggested path for doing exactly that"--